Site-selective cleavage of structured RNA by a staphylococcal nuclease-DNA hybrid. - Zuckermann, R N (1989)
A hybrid enzyme consisting of an oligodeoxyribonucleotide fused to a unique site on staphylococcal nuclease site-selectively cleaves a number of natural RNAs including Escherichia coli M1 RNA (377 bases), 16S rRNA (1542 bases), and yeast tRNA(Phe). The oligonucleotide directs the nuclease activity of the enzyme to the nucleotides directly adjacent to the complementary target sequence on the substrate RNA. In the case of M1 RNA, hydrolysis occurs primarily at one phosphodiester bond, converting 50% of the starting material to product. Furthermore, the reaction products can be enzymatically manipulated: tRNA(Phe) was cleaved in the anticodon region and was religated to form the full-length tRNA in high yield. Because the specificity of these hybrid enzymes can be easily altered, they should prove to be useful tools for probing RNA structure and function.